EP119/#992 A case-control study of adipokines in endometrial cancer and correlation with prognostic factors. (4th December 2022) - Jayraj, Aarthi S; Roy, Kallol; Singh, Neeta; Kumar, Lalit; Sharma, Daya Nand; Perumal, Vanamail; Mathur, Sandeep; Singhal, Seema; Meena, Jyoti; Khadgawat, Rajesh; Kumar, Sunesh
Abstract : Objectives: Adipokines like leptin and adiponectin play an important role in inflammation, angiogenesis, apoptosis and tumourigenesis. Such adipokines are postulated to play a role in development of obesity related cancers like endometrial cancers. We aimed to study the serum levels of leptin and adiponectin in cases of endometrial cancers and normal controls. Methods: A prospective case control study was conducted to study the serum levels of leptin and adiponectin in endometrial cancer patients and normal controls over a period of 24 months. Results: Fifty-five cases of endometrial cancers and 25 controls were included in this study. Median serum levels of leptin among cases and controls were 59.7 (16.0–485.5) ng/ml and 38.0 (4.7–107.2) ng/ml, respectively (p=0.015). Median serum adiponectin levels among cases and controls were 8481.4 (1700.7–24956.28) and 9547.5 (3015.0–24257.0) ng/ml, respectively (p=0.906). Leptin:adiponectin (L:A) ratio was significantly higher in cases than in controls (0.0086 v 0.0042, p=0.014). Due to high standard deviation of values from mean, leptin, adiponectin and L:A ratio were analysed in tertiles among cases and controls. Only age and BMI were significantly correlated with higher tertile of serum leptin and L:A ratio. Prognostic indicators like grade, stage and myometrial invasion were not correlated with leptin and adiponectin tertiles. Since lymph node metastasis was less common in our cohort, correlation with adipokines was not possible. Conclusions: Higher levels of serum leptin and lower levels of serum adiponectin seem to be positively correlated with cases of endometrial cancer. Adipokine levels did not show a correlation to histological prognostic markers.